THE IMPACT OF TECHNOLOGY-BASED INTERACTIVE ENGLISH TEACHING TOOLS ON STUDENT ENGAGEMENT AND LANGUAGE LEARNING OUTCOMES - Baxtiyorova, Nodira (Innovative Development in Educational Activities, 2023)
The impact of technology-based interactive English teaching tools on student engagement and language learning outcomes is a topic of great interest in today’s educational landscape. With the rapid advancements in technology, educators are increasingly incorporating technology-based tools to enhance teaching and learning experiences. This thesis examines the impact of technology-based interactive English teaching tools on student engagement and language learning outcomes. The study explores the benefits and challenges associated with the use of technology-based interactive teaching tools, and investigates their impact on different aspects of language learning, such as vocabulary acquisition, oral proficiency, reading comprehension and writing skills. The finding of this contribute to understanding the potential of technology-based interactive English teaching tools for enhancing student engagement and improving language learning outcomes.